1996
DOI: 10.1093/nar/24.17.3453
|View full text |Cite
|
Sign up to set email alerts
|

A short CIC-2 mRNA transcript is produced by exon skipping

Abstract: CIC-2 is a voltage- and volume-regulated chloride channel expressed in many tissues. We have shown that CIC-2 in rat lung airways is significantly down-regulated after birth [Murray,C.B. et al. (1995) Am. J. Respir. Cell Mol. Biol., 12, 597-604]. During PCR amplification from rat lung cDNA, a second transcript was identified which is 60 bp shorter than the full length sequence. The peptide translated from this 60 bp sequence contains many positively charged amino acid residues. Rat genomic DNA sequencing showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Transcript variants of the ClC-2 gene have been identified by a number of other investigators (4,5,7,10). Chu et al (4) reported the genomic structure of rat ClC-2 and identified that alternative mRNA splice variants of the rat ClC-2 gene are generated by exon skipping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcript variants of the ClC-2 gene have been identified by a number of other investigators (4,5,7,10). Chu et al (4) reported the genomic structure of rat ClC-2 and identified that alternative mRNA splice variants of the rat ClC-2 gene are generated by exon skipping.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not known whether the functional characteristics of heart ClC-2 are the same as those of brain ClC-2 in rat. In fact, short isoforms of ClC-2 mRNA transcript truncated at the C terminus due to alternative splicing were identified in multiple tissues in rat (4). Using RT-PCR, we cloned the putative full-length cDNA of ClC-2 from rat heart (rClC-2), which had 99.4% homology to the previously reported brain ClC-2 (3).…”
Section: Cloning Of Clc-2 Channels From Ratmentioning
confidence: 99%
See 1 more Smart Citation
“…Later several alternatively spliced forms were cloned from several other tissues and species, including human (Furukawa et al, 1995;Malinowska et al, 1995;Cid et al, 1995;Chu et al, 1996;Chu & Zeitlin, 1997;Furukawa et al, 1998;Cid et al, 2000;Loewen et al, 2000;Furukawa et al, 2002). Expression of ClC-2 cDNA in Xenopus oocytes or mammalian cells resulted in hyperpolarization-activated inward-rectifying Cl -currents which are sensitive to changes in cell volume and extracellular pH (Jordt & Jentsch, 1997;Furukawa et al, 1998;Park et al, 1998;Stroffekova et al, 1998;Cid et al, 2000;Park et al, 2001;Furukawa et al, 2002).…”
Section: -Channels In Cardiac Pacemaker Activitymentioning
confidence: 99%
“…Although many chloride channels of the ClC family have been cloned and expressed functionally in heterologous systems, few studies have examined the regulation of their gene expression (Shimada et al, 2000). In the family of ClC channels, ClC-2, ClC-3 and ClC-6 have been reported to have multiple isoforms (Chu et al, 1996;Chu and Zeitlin, 1997;Eggermont et al, 1997;Shimada et al, 2000). The best characterized of these is ClC-2, for which tissue-specific exon skipping and alternative splicing have been shown to generate multiple isoforms of the channel (Chu et al, 1996;Chu and Zeitlin, 1997).…”
Section: Introductionmentioning
confidence: 99%